The Jews of Denmark in the Holocaust - Fracapane, Silvia Goldbaum Tarabini, author.
1 online resource.
Keywords: Based on never previously explored personal accounts and archival documentation, this book examines life and death in the Theresienstadt ghetto, seen through the eyes of the Jewish victims from Denmark. "How was it in Theresienstadt?" Thus asked Johan Grn rhetorically when he, in July 1945, published a short text about his experiences. The successful flight of the majority of Danish Jewry in October 1943 is a well-known episode of the Holocaust, but the experience of the 470 men, women, and children that were deported to the ghetto has seldom been the object of scholarly interest. Providing an overview of the Judenaktion in Denmark and the subsequent deportations, the book sheds light on the fate of those who were arrested. Through a micro-historical analysis of everyday life, it describes various aspects of social and daily life in proximity to death. In doing so, the volume illuminates the diversity of individual situations and conveys the deportees' perceptions and striving for survival and normality'. Offering a multi-perspective and international approach that places the case of Denmark into the broader Jewish experience during the Holocaust, this book is invaluable for researchers of Jewish studies, Holocaust and genocide studies, and the history of modern Denmark.